Good governance according to Ibn Taimiyyah and it’s impression on community development - Amirullah, Muhammad Azrul; Nasution, Saipul; Kanggas, Fazari Zul Hasmi; Arif, Achmad; Wicaksana, Febrian Arif (Priviet Social Sciences Journal, 2026)
This study discusses a good governance system from the perspective of Ibn Taimiyah and its impact on community development. The type of method in this study, the author uses the library research method. This method was chosen because it facilitates the identification of research discussions. The approaches used include conceptual and legislative approaches to the subject. The data used are secondary data, obtained indirectly through library studies. This research was conducted using a qualitative approach by collecting reference sources in the form of reading books in print or online media that are related to the problem being studied. The results of the discussion show that there are several aspects of good governance or Good Governance initiated by Ibn Taimiyah, namely supporting the welfare of society in order to build good and correct governance. Therefore, Ibn Taimiyah stated that the government is an institution that builds important sectors such as politics, social, education, and economy because all of these can have a big influence on people's lives. According to him, social justice is related to human rights, so that violation of justice will cause crime and loss. Therefore, whatever form, name, or sign is used by the government and the state, as long as it helps realize social justice, must be obeyed and fully supported. Ibn Taimiyah also stated that the government as a very important institutional institution and he also stated that there are two things in determining a country and the leadership sector of the country with what it is.